Composite metal oxide target material as well as preparation method and application thereof
By preparing composite metal oxide targets doped with metal oxide and one-dimensional materials, the problems of melting and nodding of titanium-based targets during coating are solved, and the stability and coating quality are improved, and it is suitable for a variety of coating technologies.
Patent Information
- Application Number
- CN202510802287.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-08-29
AI Technical Summary
During the coating process, titanium-based targets frequently undergo melting and noduling due to phase change of α→β, which limits their application in coating processes.
A composite metal oxide target doped with metal oxide, tin oxide and titanium oxide is used to form a stable rutile phase structure by controlling the component ratio and adding one-dimensional material SiC whiskers and carbon nanotubes, thereby improving the high temperature stability and conductivity of the target.
It has achieved improvements in the stability of the target material and coating quality, reduced costs, and is suitable for various coating technologies, improving industrial efficiency.
Smart Images

Figure CN120555962A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of titanium-based target materials, and in particular relates to a composite metal oxide target material and a preparation method and application thereof. Background Art
[0002] With the rapid industrialization of electronic touch screens and solar cell thin films, the requirements for target materials are becoming increasingly stringent. Titanium-based targets, with their lower cost and environmentally friendly properties, have become one of the best candidates to replace indium-based targets and can be widely used in various thin-film electronic devices. The inherent α→β phase transition characteristics of titanium-based materials (phase transition temperature 882°C) lead to their poor stability, and melting and nodulation are frequently observed during the coating process. This will severely limit the application of titanium-based targets in coating processes such as RPD and magnetron sputtering. Therefore, the development of a method for preparing a stable, melt-resistant tin-doped titanium-based composite metal oxide target is of great practical significance. Summary of the Invention
[0003] The present invention aims to address at least one of the aforementioned technical problems in the prior art. To this end, the present invention provides a composite metal oxide target that reduces cost while ensuring stability, making it widely applicable to various coating technologies, improving industrial efficiency, and enhancing coating quality.
[0004] The present invention also provides a method for preparing the composite metal oxide target.
[0005] The present invention also provides application of the composite metal oxide target in the preparation of thin film electronic devices.
[0006] A first aspect of the present invention provides a composite metal oxide target, the components of which include doped metal oxide, tin oxide and titanium oxide.
[0007] One of the technical solutions of the present invention regarding the composite metal oxide target has at least the following beneficial effects:
[0008] At 500°C, TiO2 transforms from anatase to a rutile phase, similar to SnO2. The stability of SnO2 enhances the overall high-temperature stability of the target. Furthermore, the "skeleton" effect of SnO2 and TiO2, sharing the same rutile structure, allows the titanium-based material to support the target during the coating process, stabilizing the sublimation process. As a result, the target material of the present invention reduces costs while maintaining stability, making it widely applicable to various coating technologies, improving industrial efficiency, and enhancing coating quality.
[0009] According to some embodiments of the present invention, the mass ratio of the doped metal oxide, tin oxide and titanium oxide is (0-20%): (5-50%): (50-90%).
[0010] According to some embodiments of the present invention, the mass ratio of the doped metal oxide, tin oxide and titanium oxide is (0-10%): (35-50%): (40-65%).
[0011] According to some embodiments of the present invention, the mass ratio of the doped metal oxide, tin oxide and titanium oxide is (0.18-15%): (10-45%): (52-89.82%).
[0012] Preferably, the mass ratio of the doped metal oxide, tin oxide and titanium oxide is (0.18-6.8%): (35-45%): (55-64.82%).
[0013] Further preferably, the mass ratio of the doped metal oxide, tin oxide and titanium oxide is (0.2-5%): (35-45%): (55-64.8%).
[0014] According to some embodiments of the present invention, the doped metal oxide includes at least one of vanadium oxide, niobium oxide, tantalum oxide, antimony oxide, cerium oxide, tungsten oxide, and molybdenum oxide.
[0015] According to some embodiments of the present invention, the component further comprises a one-dimensional material.
[0016] According to some embodiments of the present invention, the one-dimensional material includes at least one of SiC whiskers and carbon nanotubes.
[0017] Among one-dimensional materials, SiC whiskers and carbon nanotubes (CNTs) themselves have super thermal stability and structural rigidity, forming a micron-reinforced network that can inhibit grain boundary slip caused by high-temperature phase change and stabilize the target material as a whole. In addition, CNTs also have extremely strong electrical conductivity, which can reduce the resistivity of the target material to a certain extent, facilitating the subsequent coating deposition process.
[0018] According to some embodiments of the present invention, the SiC whisker has a diameter of 0.1-0.5 micrometers, a length of 5-20 micrometers, and a strength of 7-10 GPa.
[0019] According to some embodiments of the present invention, the CNTs have a diameter of 1-1.5 nm, a length of 1-30 microns, and a strength of 50-100 GPa.
[0020] According to some embodiments of the present invention, the content of the one-dimensional material is 0.5-10% of the total mass of the doped metal oxide, tin oxide and titanium oxide.
[0021] The second aspect of the present invention provides a method for preparing the composite metal oxide target material according to the first aspect of the present invention, comprising the following steps:
[0022] S1: taking the doped metal oxide, tin oxide and titanium oxide powders, mixing them, adding additives to prepare a mixed slurry, drying the mixed slurry and pre-calcining it to obtain mixed powder particles, and granulating it to obtain a sintering precursor powder;
[0023] S2: pressing the sintering precursor powder into a shape to obtain a green body;
[0024] S3: sintering the green blank to obtain the composite metal oxide target.
[0025] According to some embodiments of the present invention, in step S1, the particle size of the doped metal oxide, tin oxide, and titanium oxide powder is 1-5 microns, and the purity is ≥99.99%.
[0026] According to some embodiments of the present invention, in step S1, the additives include a dispersant, a binder, and a pretreatment solvent.
[0027] According to some embodiments of the present invention, in step S1, the dispersant includes at least one of PVP and ammonium polyacrylate.
[0028] According to some embodiments of the present invention, in step S1, the amount of the dispersant added is 1-10% of the total weight of the powder.
[0029] According to some embodiments of the present invention, in step S1, the amount of the dispersant added is 0.1-5% of the total weight of the powder.
[0030] According to some embodiments of the present invention, in step S1, the binder includes at least one of PEG and PVA.
[0031] According to some embodiments of the present invention, in step S1, the amount of the binder added is 1-20% of the total weight of the powder.
[0032] According to some embodiments of the present invention, in step S1, the amount of the binder added is 5-10% of the total weight of the powder.
[0033] According to some embodiments of the present invention, in step S1, the pretreatment solvent contains a one-dimensional material.
[0034] According to some embodiments of the present invention, the pretreatment solvent containing the one-dimensional material may be deionized water containing the acid-washed modified one-dimensional material.
[0035] According to some embodiments of the present invention, the preparation process of the pretreatment solvent containing the one-dimensional material can be: take the one-dimensional material, put it into a container and soak it in concentrated nitric acid for 1-6 hours, wash it with deionized water until it is neutral, add the one-dimensional material after acid washing into deionized water and ultrasonically disperse it for 10-30 minutes to obtain the pretreatment solvent.
[0036] According to some embodiments of the present invention, in step S1, after the additives are added to form a mixed slurry, the first ball milling is performed.
[0037] According to some embodiments of the present invention, in step S1, after the first ball milling, the mixed slurry is dried, the dried powder is ground for the first time, and sieved to obtain a mixed powder having a particle size of ≤500 μm.
[0038] According to some embodiments of the present invention, in step S1, after the particle size of the mixed powder reaches the requirement, the powder is pre-calcined.
[0039] According to some embodiments of the present invention, in step S1, the pre-firing temperature is 1200-1500°C.
[0040] According to some embodiments of the present invention, in step S1, the pre-burning holding time is 2-8 hours.
[0041] According to some embodiments of the present invention, in step S1, the pre-firing environment may be normal pressure Ar gas.
[0042] According to some embodiments of the present invention, in step S1, the pre-firing includes two heat-insulating pre-firing stages. The first heat-insulating pre-firing stage adopts a mixed atmosphere of inert gas and oxygen to reduce the decomposition reaction of the oxide and stabilize the phase; the second heat-insulating pre-firing stage adopts a vacuum, reducing atmosphere or inert atmosphere to increase the number of oxygen vacancies through oxygen-depleted environment treatment, thereby reducing the resistivity of the target material and facilitating the coating deposition process.
[0043] According to some embodiments of the present invention, in step S1, the pre-fired powder has a particle size of ≤200 microns.
[0044] According to some embodiments of the present invention, in step S1, after pre-calcination, the powder is ground a second time, and after the second grinding, the powder is sieved to obtain a pre-calcined powder with a particle size of ≤200 μm.
[0045] According to some embodiments of the present invention, in step S1, after the pre-calcined powder reaches the required particle size, the powder is ball-milled for the second time.
[0046] According to some embodiments of the present invention, polyvinyl pyrrolidone (PVP), polyethylene glycol-2000 (PEG-2000), and anhydrous ethanol may be added during the second ball milling in step S1. According to some embodiments of the present invention, the first and second ball millings are performed at a rotation speed of 200-600 rpm for 6-12 hours.
[0047] According to some embodiments of the present invention, in step S1, after the second ball milling, the powder is dried and then ground for a third time to obtain mixed powder particles.
[0048] According to some embodiments of the present invention, the mixed powder particles are granulated using a granulator and sieved using a sieve to obtain a sintering precursor powder.
[0049] According to some embodiments of the present invention, the granulation method can be spray granulation, with a rotation speed of 6000-8000 r / min, a high-temperature spray granulator air inlet temperature of 150-200° C., and an air outlet temperature of 60-110° C. The sieve mesh size is 100-200 mesh.
[0050] According to some embodiments of the present invention, the particle size of the sintering precursor powder is ≤150 microns.
[0051] According to some embodiments of the present invention, the particle size of the sintering precursor powder may be 75 microns to 90 microns.
[0052] According to some embodiments of the present invention, in step S2, the sintering precursor powder is placed in a body mold and pressed into a green blank using a hydraulic press.
[0053] According to some embodiments of the present invention, the compression molding pressure is 50-200 MPa, and the molding time is 5-30 min.
[0054] According to some embodiments of the present invention, in step S3, before sintering the green blank, the process further includes degreasing the green blank.
[0055] According to some embodiments of the present invention, in step S3, the degreasing step includes: heating to 200-260°C at a heating rate of 0.5-1°C / min, holding at that temperature for 2 hours, then heating to 310-360°C, holding at that temperature for 2 hours, and then cooling at a cooling rate of 1-3°C / min.
[0056] According to some embodiments of the present invention, during the degreasing process, an argon-oxygen mixed gas with an oxygen partial pressure of 10% is passed.
[0057] According to some embodiments of the present invention, the sintering method includes: heating the temperature to 950-1400° C. at a heating rate of 5-10° C. / min and keeping the temperature for 6-8 hours.
[0058] According to some embodiments of the present invention, the sintering environment is Ar gas at normal pressure.
[0059] The third aspect of the present invention provides the use of a composite metal oxide target in the preparation of thin film electronic devices.
[0060] By controlling the target material doping ratio, the present invention can achieve a "skeleton" effect in the TiO2 target material, which also has a rutile structure, by adding 5-50% SnO2. This can support the entire target material during the coating process and stabilize the sublimation process. The addition of small amounts of vanadium oxide, niobium oxide, tantalum oxide, antimony oxide, cerium oxide, tungsten oxide, and molybdenum oxide ensures that there is no excess or overdoping during the sintering process to form a substitutional solid solution with TiO2, ensuring a more uniform target material with lower resistivity. The added SiC whiskers and CNTs have excellent thermal stability and mechanical strength. After forming a network structure within the target material, they can act as a skeleton support and will not melt during the coating process, further enhancing the stability of the target material. At the same time, the one-dimensional structure of CNTs can enhance the electrical conductivity of the target material itself, making it more suitable for use in the coating field.
[0061] The present invention utilizes micron-grade powders with a diameter of 1-5 microns and a purity of ≥99.99% as raw materials, thereby increasing target density. In subsequent processes, the sieving mesh size is increased by 100-200 mesh to avoid target cracking during sintering due to uneven powder particle size, improving target quality and reducing process costs. Regulating the pre-firing temperature and pre-firing holding time ensures a more uniform stress distribution during target pressure forming, making the target powder more stable and reducing the highly concentrated internal stress in the target during sintering, thereby preventing melting or nodules during coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is the microscopic morphology of Comparative Example 3.
[0063] Figure 2 This is the microscopic morphology of Example 1.
[0064] Figure 3 This is a real picture after coating using a commercially available conventional titanium-based target (niobium-doped titanium oxide).
[0065] Figure 4 This is a photo of the composite target material after coating using Example 1 of the present invention.
[0066] Figure 5 This is the differential scanning calorimetry spectrum of the powder before sintering in Example 1.
[0067] Figure 6 This is the XRD pattern of the powder sample of Example 1. DETAILED DESCRIPTION
[0068] The following will clearly and completely describe the concept and technical effects of the present invention in conjunction with the embodiments to fully understand the purpose, features and effects of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0069] In the description of the present invention, reference to terms such as "one embodiment," "some embodiments," "illustrative embodiments," "examples," "specific examples," or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the exemplary expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0070] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0071] Unless otherwise specified, “about” in the present invention means that the allowable error is within ±2%.
[0072] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or those recommended by the manufacturer. All reagents or instruments used, if the manufacturer is not specified, are commercially available conventional products.
[0073] Example 1
[0074] A composite metal oxide target was prepared, consisting of doped metal oxide, tin oxide, and titanium oxide. The specific preparation process is as follows:
[0075] Step 1: Pre-calcining powder mixture:
[0076] Take tantalum oxide, tin oxide, and titanium oxide powders with a particle size of about 1 micron and a purity of ≥99.99%, mix them in a mass ratio of tantalum oxide: tin oxide: titanium oxide = 3%: 29.6%: 66.4%, and add ionized water in an amount of 90% of the total mass of the powder.
[0077] The mixed slurry was ball-milled using deionized water containing 1 wt% acid-washed, modified CNTs. Zirconia balls were used for the milling process. 5% polyvinylpyrrolidone (PVP) was added before the milling process began. The mill was rotated at 300 rpm for 12 hours. After the milling, the slurry was dried in a blast dryer, ground, and sieved through a 30-mesh screen. The resulting powder had a particle size of ≤500 μm.
[0078] Step 2: Pre-sintering of mixed powder:
[0079] Once the powder reaches the required particle size, the mixture is pre-fired in a high-temperature sintering furnace at 1250°C in an atmosphere of atmospheric Ar gas for 6 hours. After pre-firing, the powder is ground a second time and sieved through an 80-mesh screen. The resulting pre-fired powder has a particle size of ≤200 microns.
[0080] Step 3: Target sintering precursor granulation:
[0081] After the pre-calcined powder reaches the required particle size, it is placed in a ball mill for a second ball milling. During the ball milling process, 5% polyvinyl pyrrolidone (PVP) and 5% polyethylene glycol-2000 (PEG-2000) are added. The solvent used in the second ball milling is anhydrous ethanol, and the amount of anhydrous ethanol added is 70% of the total powder mass. After the second ball milling is completed, the powder is placed in a blast dryer for drying. The dried powder is ground three times and granulated in a granulator at a granulation speed of 6500 r / min. The air inlet temperature of the high-temperature spray granulator is 175°C and the air outlet temperature is 75°C. The powder is sieved through a 100-mesh screen. The final sintered precursor powder has a particle size of ≤150 microns.
[0082] Step 4: Target forming process:
[0083] After the sintering precursor powder reaches the requirements, put the powder into the diameter The cylindrical mold is formed by hydraulic press with a pressure of 100MPa and a forming time of 10 minutes. Cylindrical blank.
[0084] Step 5: Target degreasing:
[0085] The formed target body is placed in a high-temperature sintering furnace for sintering. An argon-oxygen mixture with an oxygen partial pressure of 10% is passed through the furnace during the sintering process. The target body is dehydrated and degreased at a heating rate of 1°C / min. The target body is heated to 200°C and held for 2 hours. The target body is then heated to 310-360°C and held for 2 hours. The target body is then cooled at a cooling rate of 3°C / min to complete the degreasing process.
[0086] Step 6: Target material is sintered at high temperature and normal pressure:
[0087] After the debinding process is completed, the temperature is raised to 1300°C at a heating rate of 5°C / min and sintered for 7 hours in an argon atmosphere at atmospheric pressure. Finally, a composite metal oxide target is obtained.
[0088] Table 1 shows the melting conditions of the raw materials and targets produced during the reactive plasma deposition coating process for Examples 2, 3, and Comparative Examples 1 to 6. The pre-sintering process in Example 3 was carried out in stages. The first stage employed a mixed atmosphere of atmospheric pressure argon and oxygen (90%:10% by volume), a temperature of 1200°C, and a holding time of 4 hours. The second stage employed an atmospheric pressure argon atmosphere at a temperature of 1000°C and a holding time of 3.5 hours. The distance between the target and substrate in the reactive plasma deposition apparatus used was 511 mm.
[0089] Table 1
[0090]
[0091] From Table 1 we can see that:
[0092] The samples of Examples 1 to 6 (containing SnO2) generally exhibited less mass loss at 800°C than the samples of Comparative Examples 1 to 9 (excluding SnO2). None of the samples of Examples 1 to 6 melted. However, all of the samples of Comparative Examples 1 to 9 melted. This indicates that the addition of an appropriate amount of SnO2 significantly enhances the thermal stability of the material, preventing melting and reducing high-temperature mass loss (a skeleton effect).
[0093] The samples from Examples 1 to 3 (containing 1% CNTs or SiC + CNTs) exhibited minimal mass loss and excellent thermal stability. The samples from Comparative Examples 3 to 4 (without the one-dimensional material) exhibited significantly increased mass loss and even melted. This suggests that the one-dimensional material further enhances thermal stability, synergizing with SnO2 for a more effective effect.
[0094] In addition, pre-sintering treatment can significantly reduce high-temperature mass loss, possibly by stabilizing the material structure in advance.
[0095] The effect of metal oxide on thermal stability is not obvious, and its role is mainly limited to the doping function of the target. According to the test results of the four-probe, the resistivity level of the target materials of Examples 1-5 is (1~12)×10 -4 Ω·cm range. Among them, the resistivity of Example 3 is the lowest, which is 1.1×10 -4 Ω·cm. In comparison, the resistivity level of Example 6 is 6×10 -2 Ω·cm, which is a significant increase compared to Examples 1 to 5. However, this resistivity value is acceptable in the reactive plasma deposition coating process and therefore does not affect the coating process.
[0096] The resistivity of the thin film prepared by the composite target material of Examples 1-6 is in the range of (0.5 to 200)×10 -3Ω·cm. When the comparative target material was used, the melting condition was serious and no thin film was deposited.
[0097] TiO2 will transform from anatase phase to rutile phase at 500℃, just like SnO2. Figure 1 This is the microscopic morphology of Comparative Example 3. Figure 2 This is the microscopic morphology of Example 1. Figure 1 and Figure 2 It can be seen that the target material without tin oxide addition is in a molten state at the micron scale, the grain shape is irregular over a large area, and the grains are covered, coated, and overlapped in a disorderly manner; the target material with tin oxide addition shows complete and regular grains at the micron scale, and the TiO2 and SnO2 particles are evenly distributed.
[0098] Figure 3 This is a real picture of the conventional titanium-based target (niobium-doped titanium oxide) after coating. Figure 4 This is a photo of the composite target material after coating with the composite target material of Example 1 of the present invention. Figure 3 and Figure 4 It can be seen that the conventional titanium-based target materials available on the market are severely melted after the coating process, and are completely liquid or muddy molten. The target coating waste fills the entire crucible, seriously affecting the next process. Moreover, as mentioned above, no thin film is deposited using the comparative target material, indicating that the molten state also has a significant impact on the reactive plasma deposition coating state. The titanium-based target material containing tin oxide in the embodiment of the present invention exhibits the original columnar target body after coating, and can be easily taken out after cooling, without affecting the next use.
[0099] Figure 5 This is the differential scanning calorimetry spectrum of the powder before sintering in Example 1. Figure 5 It can be seen that the mixed powder has two endothermic peaks, at 200-260℃ and 310-360℃, so the degreasing step stays in these two temperature ranges to make the organic matter volatilize better.
[0100] Figure 6 It is the XRD pattern of the powder sample of Example 1 powder. Figure 6 As can be seen, the XRD pattern of the Example 1 sample exhibits characteristic peaks of the rutile phases of TiO2 and SnO2, corresponding to different crystal planes. This indicates that during the sintering process, both TiO2 and SnO2 are in the rutile phase, with no phase interference between them. Because of their identical phases, TiO2 and SnO2 more easily form a solid solution, making it easier for the thermal stability of SnO2 to achieve a skeletal effect within the TiO2 matrix, improving the target's resistance to melting and increasing production efficiency.
[0101] Although metal oxide-doped TiO2 targets have great potential in coating processes, TiO2 has many phases and is difficult to maintain in a solid state at high temperatures. Adding approximately 10% SnO2 will exhibit a skeleton effect, which significantly improves the molten state.
[0102] Both one-dimensional materials, SiC and CNTs, possess excellent thermal stability, positively impacting their resistance to melting. The difference is that SiC offers greater thermal stability but is not conductive, and excessive addition can reduce its conductivity. CNTs, on the other hand, have a short-range conductivity exceeding that of metals, enhancing both the thermal stability of the target and its electrical conductivity (although this is largely due to the metal oxide's contribution).
[0103] The pre-fired powder is more stable, which is beneficial to the upcoming sintering. The resistance of the target material after sintering is significantly reduced.
[0104] First, the various oxides will greatly complicate the conductive mechanism. The electron concentrations contained in different metal atoms are inconsistent in the body and are likely to interfere with and compensate each other. Secondly, the lattice radius and electronegativity of these metal oxides are significantly different. After adding multiple additions, they are likely to form isolated phases or non-uniform distributions in TiO2, reducing the conductivity. In addition, the sintering temperatures of different metal oxides are different. It may result in one sintering temperature not being reached while the other has already been sintered. Moreover, the difference in sintering temperature will also be reflected in the difference in thermal diffusion rate, which will reduce the density of the target material and increase the number of holes, thereby reducing the conductivity.
[0105] Targets containing both SnO2 and one-dimensional materials exhibit significant melt resistance, while targets containing only one-dimensional materials exhibit slightly less melt resistance. Targets without either SnO2 or one-dimensional materials exhibit no melt resistance at all. The pre-sintering step stabilizes the target powder, resulting in lower resistivity after sintering. Co-doping with multiple metal oxides actually increases resistivity.
[0106] After pre-firing, the metal oxide target forms a stable phase, which has two effects:
[0107] Target material density: A more stable phase is more conducive to electron transmission. For example, after pre-sintering, TiO2 transforms from anatase phase to rutile phase, which increases density, reduces pores and defects, and makes electrons easier to transmit.
[0108] Normal grain growth: Pre-sintering can reduce abnormal grain growth during the subsequent sintering process. Appropriate growth reduces the density of grain boundaries, which is more conducive to electron transport. Abnormal growth, however, can lead to uneven distribution of target grains and chaotic extension of grain boundaries, which in turn reduces conductivity.
[0109] The present invention has been described in detail above with reference to the embodiments. However, the present invention is not limited to the above embodiments. Various changes can be made within the scope of knowledge possessed by ordinary technicians in the relevant technical field without departing from the spirit of the present invention.
Claims
1. A composite metal oxide target, characterized in that: Components include doped metal oxides, tin oxide, and titanium oxide.
2. The composite metal oxide target according to claim 1, characterized in that The mass ratio of the doped metal oxide, tin oxide and titanium oxide is (0-20%): (5-50%): (50-90%).
3. The composite metal oxide target according to claim 1 or 2, characterized in that The doped metal oxide includes at least one of vanadium oxide, niobium oxide, tantalum oxide, antimony oxide, cerium oxide, tungsten oxide and molybdenum oxide.
4. The composite metal oxide target according to claim 1 or 2, characterized in that The components further include one-dimensional material; and / or the one-dimensional material includes at least one of SiC whiskers and carbon nanotubes; and / or the content of the one-dimensional material is 0.5-10% of the total mass of the doped metal oxide, tin oxide and titanium oxide.
5. A method for preparing the composite metal oxide target according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: taking the doped metal oxide, tin oxide and titanium oxide powders, mixing them, adding additives to prepare a mixed slurry, drying the mixed slurry and pre-calcining it to obtain mixed powder particles, and granulating it to obtain a sintering precursor powder; S2: pressing the sintering precursor powder into a shape to obtain a green body; S3: sintering the green blank to obtain the composite metal oxide target.
6. The method according to claim 5, characterized in that The additives include a dispersant, a binder and a pretreatment solvent.
7. The method according to claim 5, characterized in that The pre-firing temperature is 1200-1500°C.
8. The method according to claim 5, characterized in that The compression molding pressure is 50-200 MPa, and the molding time is 5-30 min.
9. The method according to claim 5, characterized in that The sintering method comprises: heating to 950-1400° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 6-8 hours.
10. Use of the composite metal oxide target according to any one of claims 1 to 4 in the preparation of thin film electronic devices.